The Removal of Copper and Iron from Wine Using a Chelating Resin - Loubser, G.J.; Sanderson, R.D. (South African Journal of Enology and Viticulture, 2017)
An insoluble polymer-supported absorbant, developed for the selective removal of excess copper and iron from wine was tested. Tests conducted on dry white wine with excessive copper and iron showed effective removal of 98% copper (II) and 82 % iron (III). This treatment did not significantly affect the other wine constituents and therefore offers an appropriate alternative to the ferrocyanide treatment.